PENEGAKAN HUKUM TERHADAP PELANGGARAN LALU LINTAS DI POLRES MINAHASA UTARA MENURUT UNDANG-UNDANG LALU LINTAS DAN ANGKUTAN JALAN - Joke Punuhsingon; Karno M.S. Rumondor; Nopesius Bawembang; Julius Kindangen; Rohyani Rigen Is Sumilat; Jocefina Adelleyda Tendean (Fakultas Hukum Univesitas Kristen Indonesia Paulus, 2023)
ABSTRACT This research examines and answers Law Enforcement Against Traffic Violations at the North Minahasa Police According to the Traffic and Road Transportation Law and how to solve them. The research conducted included normative juridical research and is descriptive analysis in nature, using primary and secondary data. The author uses primary legal materials, namely Law no. 2 of 2002 concerning the Indonesian National Police and Law No. 22 of 2009 concerning Road Traffic and Transportation. Law Enforcement Against Traffic Violation Crimes at North Minahasa Police is currently still weak, especially related to the increasing quantity of violations, also related to the ability to understand public awareness in traffic. The urgency of this transportation can be seen in the frequency of the need for the use of transportation services for the mobilization of people as well as goods to remote parts of the country, even from and to other countries. Simultaneously, transportation also has a role in supporting, encouraging, and driving the growth and development of regions that have potential, but have not yet grown, for efforts to increase the distribution of development and its res